Travel for elite athletes during COVID-19 - A graphical guide (British Journal of Sports Medicine, 2021)
This graphical guide outlines current evidence-based recommendations on travelling in elite sport during the coronavirus pandemic. This serves only as a guide; given the dynamically changing situation, any newly released recommendations should be taken into account.